SUBSTANCE USE AMONG COLLEGE STUDENTS IN JAKARTA: BETWEEN REHABILITATION AND LAW ENFORCEMENT - Baby Poernomo; Ade Tuti Turistiati (Adisam Publisher, 2023)
Substance use among college students in Jakarta are increasing in number. The rise of student behavior deviations can endanger the survival of the nation in the future, because students are expected to be the nation's leaders. The fragility of youth undermined by addictive substances destroying nerves makes them unable to think and work. As a result, our young generation will only become an unproductive society. Until now the handling of drug abuse cases among students still becomes pros and cons. Students who are exposed to drug cases are not all directly rehabilitated but there are also those who are first processed legally and must be imprisoned. This study aims at answering the questions why the handling of drug abuse cases among students still vary in application which led to pros and cons in society and how to save our young generation from drug abuse so that they can return to the society and contribute to their nation. This study employed a phenomenological approach of a qualitative research design. In this study a semi-structured interview is used to understand how participants experienced the phenomenon. Data were gathered from a total of 15 participants consist of college students, leaders of universities, an official of BNN (National Board of Narcotics and Addictive Substances), Head of prison, and a law practitioner to get the perspectives on how rehabilitation and law enforcement should be implemented. The research proved that the implementation of coersive action in the form of rehabilitation and law enforcement has not been fully implemented properly. This study provides insight into a view to improve the system of handling substance users among college students and offers recommendations for future research.